Starch Trek: The Search for Yield - Lloyd, James R.; Kossmann, Jens (Frontiers in Plant Science, 2019)
Starch is a plant storage polyglucan that accumulates in plastids. It is composed of two polymers, amylose and amylopectin with differing structures and plays several roles in helping to determine plant yield. In leaves it acts as a buffer for night time carbon starvation. Plants that are unable to synthesize starch, or which degrade it poorly, grow less well than wild-type plants. There have been a number of successful approaches to manipulate leaf starch metabolism that have resulted in increased growth and yield. Its degradation is also a source of sugars that can help alleviate abiotic stress. In edible parts of plants, starch often makes up the majority of the dry weight constituting much of the calorific value of food and feed. Increasing starch in these organs can increase this as well as increasing yield. Enzymes involved in starch metabolism are well known and there has been much research analyzing their functions in starch synthesis and degradation, as well as genetic and post-translational regulatory mechanisms affecting them. In this mini review we examine work on this topic and discuss future directions that could be used to manipulate this metabolite for improved yield.